11r2-r-2=0

Simple and best practice solution for 11r2-r-2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11r2-r-2=0 equation:



11r^2-r-2=0
We add all the numbers together, and all the variables
11r^2-1r-2=0
a = 11; b = -1; c = -2;
Δ = b2-4ac
Δ = -12-4·11·(-2)
Δ = 89
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$r_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$r_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$r_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-1)-\sqrt{89}}{2*11}=\frac{1-\sqrt{89}}{22} $
$r_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-1)+\sqrt{89}}{2*11}=\frac{1+\sqrt{89}}{22} $

See similar equations:

| -3(w+5)+4w+2=16 | | 5z-43=7z+7 | | (2x+1)(5x+2)=0 | | x10+2=6 | | 2y+12=2(y+6) | | 10x-4=6x+8* | | 4a-15=3a+2 | | 28=12+4b | | 3x=8=-40-5x | | (y-4)^(2/5)-3=1 | | 7x+5=10(x-7-3x | | z8+1=1 | | 17t=16t+2 | | 5(9x-2)=3(x+4) | | -x-2=4x-1 | | (6x=7)*(3x+5) | | t+5-6=16 | | C=77+29h | | 25=6k-4 | | .4x-1=2-2.6+2x | | 1/3(6x-12)-5x=4 | | (5x+1)(x+1)=0 | | 8.1=0.9h | | 5s+2s-5s+s=15 | | 81^3x-3=729^x+2 | | a+3+1=16 | | 2x-3=11x-31 | | 4.7=r/3.2 | | -42x=4x-76 | | 8c+3c-3c-3c-c=4 | | 3(8x+1)=-12 | | 3x0=1 |

Equations solver categories